Opening New Avenues... Soilless cultivation of vegetables brings opulence - Singh, P K; Singh, Lokendra; Patel, Neelam (Indian Horticulture, 2019)
Soilless cultivation mainly refers to techniques of hydroponics and aeroponics. Hydroponics is a method of growing plants using mineral nutrient solution, without soil with their roots immersed in nutrient solution. Terrestrial plants may be grown with their roots in mineral nutrient solution only or in an inert medium, such as perlite, gravel or mineral wool. This system helps to face the challenges of climate change besides helping in production system management for efficient utilization of natural resources and mitigating malnutrition. Aeroponics is another technique more or less similar to hydroponics with only difference that under aeroponics plants are grown with fine drops of nutrient solution.